The Use Of Short Movies Taken From Blake Ridder Youtube Channel In Improving Students’ Vocabulary At Smk Muhammadiyah 1 Wonosobo - Ullimti Hikmata Hamzani; Rochyani Lestiyanawati (Jurnal Reflektif, 2024)
This study aims to determine the effectiveness of using short movies from Blake Ridder's YouTube channel in improving vocabulary skills of grade 10th students at SMK Muhammadiyah 1 Wonosobo. This study uses experimental quantitative research method with two classes, namely experimental class (10th PPLG 1) and control class (10th PPLG 2). Researchers use pre-test and post-test to measure students' abilities, in the form of essay questions for writing skills. The results shows that the vocabulary ability of the experimental class students increases by 55% after using short movies, while the control class increases by 20%. These results show that the use of short movies can significantly improve students' vocabulary skills. Therefore, it is recommend to use short movies as teaching materials in improving students' vocabulary skills.